2007
DOI: 10.1007/s10103-007-0503-5
|View full text |Cite
|
Sign up to set email alerts
|

Erbium, chromium:yttrium scandium gallium garnet laser for caries removal: influence on bonding of a self-etching adhesive system

Abstract: This study evaluated the influence of the dental substrates obtained after the use of different caries removal techniques on bonding of a self-etching system. Forty, extracted, carious, human molars were ground to expose flat surfaces containing caries-infected dentine surrounded by sound dentine. The caries lesions of the specimens were removed or not (control--G1) either by round steel burs and water-cooled, low speed, handpiece (G2), or by irradiation with an erbium, chromium:yttrium scandium gallium garnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
14

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 26 publications
2
42
0
14
Order By: Relevance
“…Since Clearfil SE bond used in current study is categorized in mild self-etching bonding system according to its acidity (pH = 1.8), the μ TBS of laser-irradiated Clearfil SE bond group was the lowest of all tested groups. Other authors 23,33) also support this finding that the Er,Cr:YSGG laser-irradiated dentin is poor substrate for bonding with the self-etching system. For example, Cardoso et al 23) assessed the bonding effectiveness of adhesives to Er,Cr:YSGG laser-irradiated dentin using irradiation settings specific for cavity preparation, and demonstrated that the bond strength of Optibind FL (three-step total-etch) was the highest, followed by Clearfil SE bond (two-step self-etch), Clearfil S3 bond and Adper Prompt L-Pop (one-step self-etch).…”
Section: ⅳ Discussionmentioning
confidence: 72%
“…Since Clearfil SE bond used in current study is categorized in mild self-etching bonding system according to its acidity (pH = 1.8), the μ TBS of laser-irradiated Clearfil SE bond group was the lowest of all tested groups. Other authors 23,33) also support this finding that the Er,Cr:YSGG laser-irradiated dentin is poor substrate for bonding with the self-etching system. For example, Cardoso et al 23) assessed the bonding effectiveness of adhesives to Er,Cr:YSGG laser-irradiated dentin using irradiation settings specific for cavity preparation, and demonstrated that the bond strength of Optibind FL (three-step total-etch) was the highest, followed by Clearfil SE bond (two-step self-etch), Clearfil S3 bond and Adper Prompt L-Pop (one-step self-etch).…”
Section: ⅳ Discussionmentioning
confidence: 72%
“…Çürükten etkilenmiş dentinde elde edilen bağlanma dayanımı değerleri normal dentin ile kıyaslandığında genellikle daha düşüktür. [23][24][25] Literatürde çürük dişler kullanılarak yapılan çalışmalara bakıldığında farklı sonuçlar görülmektedir. Singh UP ve ark.…”
Section: Gereç Ve Yöntemunclassified
“…As observed by Tachibana et al using SEM, irradiated dentin presented opened dentinal tubules, with protruded peritubular dentin distributed on a scaly surface, free of a smear layer. 36 These characteristics are considered ideal for bonding to dentin. In this case, the laser irradiation initially vaporizes the water and other hydrated organic components of the tissue.…”
mentioning
confidence: 99%
“…This modification could produce a dentin surface more resistant to demineralization, impairing the action of the mild pH hydrophilic primer used. 36 Fracture behavior is another property that defines the bonding of dentin to ceramic. The failure mode with the Acid + Variolink II (control) and Clearfil groups was mainly cohesive in dentin fracture.…”
mentioning
confidence: 99%
See 1 more Smart Citation